Validation of a Multidimensional HR Flexibility Measure - Way, Sean A.; Tracey, J. Bruce; Fay, Charles H.; Wright, Patrick M.; Snell, Scott A.; Chang, Song; Gong, Yaping (Journal of Management, 2015)
Wright and Snell (1998) contend that HR flexibility is an important construct that may enable managers and management scholars to gain a greater understanding of the role of human resource management in enhancing firm performance. However, there is limited evidence regarding the psychometric properties of the measures that have been used to assess the HR flexibility construct and examine its effects. A primary objective of this study was to develop and validate a psychometrically sound measure of the HR flexibility construct. In this article, we present evidence of content validity/adequacy, internal consistency reliability, convergent validity, discriminant validity, and criterion-related validity that provides support for the use of this study’s multidimensional HR flexibility measure in subsequent empirical inquiries and theory testing efforts. Implications and limitations of this current research as well as avenues for future research are discussed.